How electronic health literacy influences physical activity behaviour among university students: A moderated mediation model - Ning Zhou; Fanzheng Mu; Yao Zhang; Dingyou Zang; Weidong Zhu; Xiaoyu Wang; Wei Wang; Haoyu Li; Jiaqiang Wang; Xingyu Zhang; Chenxi Li; Yuhan Li; et al. (PLoS ONE, 2025)
Purpose This study examines how eHealth literacy influences exercise behaviour among university students through a moderated mediation model. Specifically, peer relationships are positioned as mediators, while sleep quality moderates the effect of eHealth literacy on exercise behaviour among university students. The study explores the intricate interactions involved and elucidates how eHealth literacy affects exercise behaviour through multiple dimensions. Methods Student data were collected via questionnaire surveys across multiple academies. A stratified purpose sampling approach was employed for participant selection, targeting four specific universities to ensure regional and typhological representation: Nanjing Xiaozhuang University, Yangzhou University, Shangqiu University, and Yangzhou Polytechnic Institute. This process resulted in 14,892 valid responses for analysis, and SPSS 26.0 along with the PROCESS macro was used to analyses variables such as electronic health literacy, physical activity, sleep quality, and peer relationships. Results The structural equation modeling revealed a significant direct effect of eHealth literacy on university students physical activity behaviour (β=0.065, p<0.001). Mediation analysis delineated an indirect pathway through peer relationships: eHealth literacy significantly enhanced peer relationship quality (β=0.251, p<0.001), which subsequently predicted increased physical activity (β=0.058, p<0.001). Peer relationships significantly mediate between eHealth literacy and university students physical activity (β=0.251, p<0.001). Additionally, sleep quality serves as a moderating variable (β=0.029, p<0.001), significantly moderating the direct effect of eHealth literacy on university students physical activity, with the 95% confidence intervals consistently excluding zero. Conclusion EHealth literacy among university students can significantly and positively predict their exercise behaviour. Peer relationships mediate the effect of eHealth literacy on exercise behaviour. At the same time, sleep quality is a moderating variable influencing eHealth literacy's direct impact on university students exercise behaviour.